LCL-Filter Design Based on Modulation Index for Grid-Connected Three-Level Hybrid ANPC Inverters - Jo, Ha Rang; Kim, Ye Ji; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2021)
This paper proposes an LCL-filter design based on the modulation index for grid-connected hybrid active neutral point clamped (ANPC) inverters. The three-level hybrid ANPC inverter consists of silicon insulated gate bipolar transistors and silicon carbide metal oxide semiconductor field effect transistors to reduce the switching losses. LCL-filter parameters for the three-level hybrid ANPC inverter are calculated using the current ripple factor. The current ripple factor is affected by phase voltage, which varies according to the modulation index, and therefore the inductance on the inverter side must be considered with the modulation index. To design inductance on the inverter side, the output phase voltage and grid voltage are used to analyze the current ripple factor. The filter capacitor and the inductance on the grid side are designed based on the reactive power absorption and current ripple attenuation. The effectiveness of the proposed LCL-filter design method is validated via simulation and experimental results.
Keywords: Active neutral point clamped; Current ripples; Filter capacitors; Grid voltage; Grid-connected; Phase voltage; Power absorption; Switching loss; Hybrid active neutral point clamped (ANPC); LCL-filter design; Modulation index; Silicon carbide (SiC)